2005
DOI: 10.1080/02652030500090885
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of paper and board food packaging: Chemical analysis and genotoxicity of possible contaminants in packaging

Abstract: In order to identify potential genotoxicant(s) in recycled paperboard, samples were fractionated using multiple liquid/liquid extraction, and gel permeation chromatography, and analysed by gas chromatography/mass spectrometry and liquid chromatography/mass spectrometry. The rec-assay was used as an indicator of genotoxicity. Genotoxicants in the recycled paperboard were identified as dehydroabietic acid (DHA) and abietic acid (AA). DHA and AA were detected in two out of five virgin products, and in all seven r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Studies have reported different fractionation strategies for extracts from paper and board samples, such as filtering or by several liquid-liquid extractions followed by gel permeation chromatography (Ozaki et al 2005;Bradley et al 2008). In comparison with these methods, an advantage of using an HPLC-based fractionation method is that the separation process can be further optimised, e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported different fractionation strategies for extracts from paper and board samples, such as filtering or by several liquid-liquid extractions followed by gel permeation chromatography (Ozaki et al 2005;Bradley et al 2008). In comparison with these methods, an advantage of using an HPLC-based fractionation method is that the separation process can be further optimised, e.g.…”
mentioning
confidence: 99%
“…This makes it possible to separate substances that co-elute in one fractionation round into several sub-fractions in a second fractionation round. The use of several liquid-liquid extractions, as described by Ozaki et al (2005), is not compatible with in vitro assays due to the cytotoxicity of the solvents used. Vaporising the non-compatible solvent and re-dissolving the extracted compounds with a compatible solvent would be futile as the extracted compounds would have a different solubility with this new solvent.…”
mentioning
confidence: 99%
“…Diisopropyl naphthalene constitutes the solvent ink capsules of carbonless copy paper and thus is generally present in paper from municipal waste collection . Phthalates are ubiquitous contaminants, but their migration from packaging into food is thought to be the main exposure source, since they are mainly used as adhesives in pulp, paper and board production . Diisobutyl phthalate (DIBP) and bis(2‐ethylhexyl) phthalate are also used as plasticizers in dispersion glues and printing inks .…”
Section: Resultsmentioning
confidence: 99%
“…Only recently whole packaging migrates from different FCMs have been studied for their overall toxicity [15,16,47,[52][53][54]. It is noteworthy that in all studies effects of the whole leacheate were observed that could not be explained only by the known toxicity of identified or putative mixture components.…”
Section: New Toxicological Paradigms Of Relevance For Fcm Effect Assementioning
confidence: 99%